The Wizard of Oz - LeRoy, Mervyn; Metro-Goldwyn-Mayer. ([New York] MGM/UA Home Video, 1991)
Transported to the land of Oz by a tornado, Dorothy journeys along the yellow brick road with her friends, the scarecrow, the tin woodman and the cowardly lion to ask help from wizard with their problems.
DVD
Music by Harold Arlen; film editor, Blanch Sewell
Judy Garland, Frank Morgan, Ray Bolger, Bert Lahr, Jack Haley, Billie Burke, Margaret Hamilton
Keywords: Feature films